Effects of size and concentration on diffusion-induced stress in lithium-ion batteries - Ma, Z.; Gao, X.; Wang, Y.; Lu, Chunsheng (American Institute of Physics, 2016)
Capacity fade of lithium-ion batteries induced by chemo-mechanical degradation during charge-discharge cycles is the bottleneck in design of high-performance batteries, especially high-capacity electrode materials. Stress generated due to diffusion-mechanical coupling in lithium-ion intercalation and deintercalation is accompanied by swelling, shrinking, and even micro-cracking. In this paper, we propose a theoretical model for a cylindrical nanowire electrode by combining the bond-order-length-strength and diffusion theories. It is shown that size and concentration have a significant influence on the stress fields in radial, hoop, and axial directions. This can explain why a smaller electrode with a huge volume change survives in the lithiation/delithiation process.